Economic benefit use of the service "National Natural Parks of Ukraine" on the formation of objects of the natural reserved fund - Bugaenko, I. (Land Management, Cadastre and Land Monitoring, 2019)
The stages of forming the National Natural Parks (NPP) swere investigated. The stages of NPP formation, which are carried out in accordance with environmental and land legislation, were specified. The completion time and the cost of each stage were highlighted. The long process of forming the NPPs, the high cost of preparing technical documentation, bureaucratic obstacles at the stages of project documentation approval prove the ineffectiveness of the current system of forming the NPPs. the ineffectiveness of the today’s system of NPP formation is proved by the fact that during the years of Ukraine’s independence only 5.72% of the NPPs were formed. Bureaucratic obstacles at the stages of NPP formation lead to wasteful spending of funds from the State Budget of Ukraine, and Soviet methods for their formation lead to the loss of valuable natural territories. As a result, no environmental protection activities are carried out in the NPPs, the share of the state’s ecological component decreases and the population’s standard of living decreases. An effective modern electronic GIS method for forming the NPP swas proposed. Its effectiveness was proved: project and cartographic documentation is elaborated in 100% compliance with the Presidential Decree, the stages of formation are performed almost free of charge and faster by 87.5% in comparison with the existing method. Time and economic indicators, methods of forming the NNP swere compared. The advantages of modern electronic GIS method were substantiated. Key words: service of Ukraine’s NPPs, stages of NPP formation, Minpryrody, State Land Cadastre (SLC), creation plan, management plan, land management plan, Setting-Out Plan, economic indicators, time indicators.